THE COMPARISON BETWEENTHE METHODS OF DPPH AND FRAP APPLIED TO ASSESS THE ANTIOXIDANT ACTIVITY OF THE GOLDEN SNAIL EGG EXTRACT (Pomaceae cannaliculata) - Yolanda Pridatama; Mirna Ilza; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract               The study aimed to compare the using of DPPH and FRAP methods to assess the antioxidant activity of the golden snail egg extract(Pomaceae cannaliculata)and to determine the chemical composition contained in the golden snail eggs. The parameters tested were proximate analysis (the content of moisture, ash, protein, fat, and carbohydrate) (AOAC, 2005), extract yield (Karnila et al., 2011), secondary metabolite test and antioxidant activity test on golden snail egg extractby using DPPH method compared to FRAP method. There were significant differences between the values of the antioxidant activity of the golden snail egg extract assessed by using the DPPH and FRAP methods. The best value of antioxidant activity was obtained by using the DPPH method with the value of IC50at 220.02 ppm, lower than it by using the FRAP method. The snail egg extract contained water 10.14%, ash 44.02%, protein 33, 38%, fat 0.11% and carbohydrates 12.34% (by difference). Keywoards: Antioxidant, DPPH, FRAP, golden snail egg